MOKE and MFM on magnetically coated nanofiber mats: Transferring well‐known methods to uncommon samples. Issue 2 (6th February 2023) - Brocks, Oliver; Stasiak, Adam; Biedinger, Jan; Wortmann, Martin; Blachowicz, Tomasz; Kaschuba, Reinhard; Ehrmann, Andrea
Abstract: The hysteresis loops of magnetic samples can be measured by the magneto‐optical Kerr effect (MOKE), while magnetic force microscopy (MFM) is used to depict domain walls or spatially resolved magnetization orientation in magnetic nanostructures or thin films. Both methods are commonly applied on thin films with a perfectly flat surface or on nanostructures. Here, we report MOKE and MFM measurements on a new class of magnetic materials, namely electrospun mats of randomly oriented nanofibers which influence the 30 nm Co coating layer, proving especially the MOKE method utilizable for rough surfaces. Possible interpretations of these first MOKE measurements on highly randomly structured magnetic layers are given. Abstract : Magneto‐optical Kerr effect (MOKE) and magnetic force microscopy measurements on magnetically coated nanofiber mats are shown for the first time. These techniques offer new possibilities to investigate the magnetic properties of highly uneven substrates.